PERAN ORANG TUA TERHADAP PENDIDIKAN KARAKTER ANAK USIA DINI - Susi Fatmala (Universitas Muhammadiyah Surabaya, 2022)
Character education should be carried out from an early age to children, because earlyÂ childhood is the golden age of early childhood development whose success will determine the qualityÂ of children in their adult years. So, the role of parents is very important in providing character educationÂ to early childhood. The purpose of this study is to describe the importance of the role of parents inÂ character education for early childhood. The method in this study uses the method of library researchÂ (library research). The results of the study indicate that the role of parents is a determining factor forÂ the development of children both physically and mentally, because the role of both parents is the firstÂ and foremost educator for children who are born until they grow up. In providing knowledge through. parenting conveyed by parents is very important. Education in the family plays a very important role inÂ developing children's character, personality, morals, religious and cultural values, and simple skills. TheÂ role of a parent in influencing the character of a child is no longer borne by the mother. The role of theÂ father in the formation of the child's character is also very large, the father is still obliged to take careÂ of and interact with his child, such as inviting him to talk, joke, and play.Â Keywords: The role of parents; early childhood; character education